1998
DOI: 10.1093/oxfordjournals.aje.a009678
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Blood Pressure Trends in US Adults between 1960 and 1980 Influence of Antihypertensive Drug Therapy

Abstract: Recent blood pressure trends reflect progress in hypertension control, but prevalent drug therapy precludes direct estimation of the component due to primary prevention. In data gathered on persons aged 35-74 years in three successive US health examination surveys (1960-1980), systolic blood pressure levels assuming no drug therapy were imputed by reassigning blood pressure to the upper end of the distribution for respondents reporting use of antihypertensive medication. Blood pressure was partitioned into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…We found that a value close to 130/80 mmHg was above the 95th centile and that parity, age and body mass index at first visit had a significant influence on blood pressure in Caucasians. That blood pressure increases with age and body mass index is well known from population studies 4,14–17 . Blood pressure levels were slightly lower in Asians and Blacks than Caucasians despite a similar age across all ethnic groups, possibly because in our population Asians had a lower body mass index and Blacks a higher number of multiparae than Caucasians.…”
Section: Discussionsupporting
confidence: 46%
“…We found that a value close to 130/80 mmHg was above the 95th centile and that parity, age and body mass index at first visit had a significant influence on blood pressure in Caucasians. That blood pressure increases with age and body mass index is well known from population studies 4,14–17 . Blood pressure levels were slightly lower in Asians and Blacks than Caucasians despite a similar age across all ethnic groups, possibly because in our population Asians had a lower body mass index and Blacks a higher number of multiparae than Caucasians.…”
Section: Discussionsupporting
confidence: 46%
“…As an occupational cohort, our sample is likely to be healthier than the general population of the same age and sex as individuals with severe illness or disability will not have been selected for army service. Comparison of mean levels of selected physiological risk factors in the men in our sample with those obtained from men of a similar, but not identical age range, in the second National Health Nutrition and Examination Survey (1976–80) suggest that the men in our sample have slightly lower systolic blood pressure36 and a lower prevalence of obesity,37 but differ little as regards total or HDL cholesterol 38. We have no means of knowing whether our sample differed in mean IQ scores from the national population of men of this age, but it is likely that men with the lowest scores will be under-represented because the test taken during selection for the army was designed to detect intellectual deficits 11.…”
Section: Discussionmentioning
confidence: 57%
“…This likely reflects differences in the circumstances of measurement since, as far as we know, no medication to slow the pulse rate spread rapidly between the early 1970s and the early 1980s. Medication may, however, explain the decline in average blood pressure over this period (Kumanyika et al 1998). As a further check, we also analyze self-reported hypertension.…”
Section: Resultsmentioning
confidence: 99%